Mobile POS and Web Inventory System - Jephtah Sustituido (IC-ITECHS, 2020)
POS has been essential to the computer age where calculations and computations are necessary and must be efficient, reliable, accurate, and convenient to the small businesses going to big businesses. On the other hand, the inventory has been also a necessity Mobile POS and Web Inventory System to a growing business and big businesses as products keeps going in and out, minute by minute, and product must be monitored and regulated efficiently and accurately in order for an error to be minimized. As this study is concerned, most small and growing businesses do not use a POS system nor Inventory System, as to why there is a huge margin of error in terms of computations and calculations of the products and product sales. By conducting this study, looking for an efficient and reliable system was difficult to approach as many businesses cannot fully afford this kind of systematic approach to their essential need in order for the business to grow furthermore. As this study concludes, POS system and Inventory system must be reliable, efficient, convenient, accurate, and affordable. And for that reason, the study aims to build a system combining POS system and Inventory system in one system that can be accessed easily anywhere else securely, fast and user friendly. In this pattern, the POS system will be accessed through Android phones as such phones that have a camera that can scan QR code of the product and the Inventory System will be accessed through website application in a computer in a secured manner. This study provides the most affordable and efficient system that can provide support to the growing businesses and small businesses.